KESANTUNAN BERBAHASA DALAM MASYARAKAT OSING DI KABUPATEN BANYUWANGI - Dwi Astutik; Akhmad Sofyan; Asrumi Asrumi; Bambang Wibisono; Ali Badrudin (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
The use of the Osing language in this area is still quite strong, and the pronunciation could be more precise. Even so, the people of this village still apply politeness in language when interacting with each other. This study aimed to find out the forms and language politeness strategies used by the Osing community in Macan Putih Village. This research method uses a qualitative research method with three stages: the stage of providing data, the stage of data analysis, and the stage of providing the results of data analysis. The research data is in utterances by speech participants associated with a context. The study results show that most of the Osing people in Macan Putih Village are polite in speaking, although some still violate it. The form of politeness in the language of the Osing community is based on markers of politeness verbally through speech and nonverbally through accompanying body gestures, as well as the politeness scale. There are two strategies namely positive politeness strategies such as (1) paying attention, (2) exaggerating in giving comments or praise, (3) using markers as members of the same group, (4) using jokes, and (5) giving questions or asking for reasons. The second strategy is the negative politeness strategy, namely (1) using indirect speech, (2) being pessimistic, and (3) minimizing coercion/pressure.